A new empirical model for residual flexural capacity of corroded post-tensioned prestressed concrete beams. (December 2021) - Lu, Zhao-Hui; Zhou, Qi-Hao; Li, Hai; Zhao, Yan-Gang
Abstract: In this paper, a total of 70 experimental flexural tests of corroded post-tensioned prestressed concrete (PC) beams were gathered from the published literatures. Using the experimental data, a comprehensive databank of flexural capacity of the corroded PC beams was established. Meanwhile, four existing empirical models for calculating the residual flexural strength of the corroded PC beams were also gleaned and contrasted with each other based on the databank. It turns out that three of the four existing empirical models underestimate the flexural capacity. To deeply analyze the factors affecting the flexural capacity, numerous factors were discussed, e.g., the corrosion ratio, beam width, effective height of the beam section, concrete compressive strength, and the ratio of strength between the tensile reinforcement (including prestressed and non-prestressed reinforcement) and concrete. It is found that the corroded post-tensioned PC beams' residual flexural capacity is affected most by the corrosion ratio. In the end, a better empirical model is proposed for computing the residual flexural capacity of corroded PC beams, which provides accurate and effective predictions in a wide range of corrosion ratio for engineering practice.